2020
DOI: 10.1111/jcmm.15500
|View full text |Cite
|
Sign up to set email alerts
|

CD73 acts as a prognostic biomarker and promotes progression and immune escape in pancreatic cancer

Abstract: CD73 is a glycosylphosphatidylinositol (GPI)‐anchored protein that attenuates tumour immunity via cooperating with CD39 to generate immunosuppressive adenosine. Therefore, CD73 blockade has been incorporated into clinical trials for cancers based on preclinical efficacy. However, the biological role and underlying mechanism of CD73 in pancreatic cancer (PC) microenvironment and its prognostic impact have not been comprehensively studied. In this article, we found that the expression of CD73 was up‐regulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 48 publications
1
62
0
Order By: Relevance
“…In one study on two PDAC cell lines (and other cancer cell lines) it was shown that stimulation of A 2B receptor reduced cell–cell contact and increased cell scattering, implicating its role in metastatic spreading [ 146 ]. Gene expression analysis of pancreatic cancer tissues based on TCGA and GTEx databases (The Cancer Genome Atlas and Genotype-Tissue Expression projects) showed that both ADORA2A and ADORA2B were significantly upregulated [ 147 ]. Interestingly, analysis of TCGA database, indicates that the high expression of ADORA2B is associated with poor survival, while high expression of ADORA2A is associated with significantly better survival [ 74 ].…”
Section: Purinergic Signaling In Pancreatic Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…In one study on two PDAC cell lines (and other cancer cell lines) it was shown that stimulation of A 2B receptor reduced cell–cell contact and increased cell scattering, implicating its role in metastatic spreading [ 146 ]. Gene expression analysis of pancreatic cancer tissues based on TCGA and GTEx databases (The Cancer Genome Atlas and Genotype-Tissue Expression projects) showed that both ADORA2A and ADORA2B were significantly upregulated [ 147 ]. Interestingly, analysis of TCGA database, indicates that the high expression of ADORA2B is associated with poor survival, while high expression of ADORA2A is associated with significantly better survival [ 74 ].…”
Section: Purinergic Signaling In Pancreatic Cancermentioning
confidence: 99%
“…Adenosine A 3 receptors are the most studied adenosine receptors in several cancers, and opposing effects can be found ranging from anti-tumoral effects to those promoting metastasis [ 3 ]. A 3 receptor is upregulated in breast and colon tumor tissues compared to the adjacent normal tissue, but the number of samples from pancreas was limited to reach any conclusion in one study [ 152 ], but gene expression analysis of pancreatic cancer tissues based on TCGA and GTEx databases shows that also ADORA3 is upregulated compared to normal pancreas [ 147 ]. Recent interesting papers [ 153 , 154 ] show that adenosine, A 3 R, and mast cell—cancer cell interactions may constitute an important part in TME.…”
Section: Purinergic Signaling In Pancreatic Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…A dramatic upregulation of CD73 in PAAD compared to the matched normal tissue ( Figure 1 B) was related to a high histological grade, a well-established indicator marking the degree of tumor differentiation ( Figure 2 D). In an independent PAAD dataset, CD73 expression was shown to be upregulated in both (classical and basal) subtypes of pancreatic cancer [ 66 ]. DNA methylation of CD73 was lower in tumors compared with matched normal pancreatic tissue.…”
Section: Cd73 and Tumor Plasticitymentioning
confidence: 99%
“…In cancer, CD73 is expressed by many subsets of cells populating the tumor lesion, including tumor cells, stromal cells, and endothelial cells, as well as infiltrating immune cells ( Vijayan et al, 2017 ). High CD73 tumor expression is associated with shorter overall survival and poor prognosis of patients with melanoma ( Monteiro et al, 2018 ), diffuse large B-cell lymphoma ( Wang et al, 2019 ), breast cancer ( Loi et al, 2013 ; Turcotte et al, 2017 ; Buisseret et al, 2018 ; Jiang et al, 2018 ), ovarian cancer ( Turcotte et al, 2015 ; Jiang et al, 2018 ), head and neck cancer ( Mandapathil et al, 2018 ), head and neck squamous carcinoma ( Ren et al, 2016 ) non–small-cell lung cancer ( Inoue et al, 2017 ), thyroid carcinoma ( Bertoni et al, 2019 ), pancreatic cancer ( Chen et al, 2020 ), gastric cancer ( Lu et al, 2013 ), or colorectal cancer ( Wu et al, 2012 ). Of note, the up-regulation of CD73 in cancer patients has been addressed as a mechanism of resistance to antitumor therapies.…”
Section: Membrane-bound Cd73 In Cancer Patientsmentioning
confidence: 99%